Breakdown of the efficiency gap to 29% based on experimental input data and modeling. (10th October 2015) - Brendel, Rolf; Dullweber, Thorsten; Peibst, Robby; Kranz, Christopher; Merkle, Agnes; Walter, Daniel
Abstract: We demonstrate a procedure for quantifying efficiency gains that treats resistive, recombinative, and optical losses on an equal footing. For this, we apply our conductive boundary model as implemented in the Quokka cell simulator. The generation profile is calculated with a novel analytical light‐trapping model. This model parameterizes the measured reflection spectra and is capable of turning the experimental case gradually into an ideal Lambertian scheme. Simulated and measured short‐circuit current densities agree for our 21.2%‐efficient screen‐printed passivated emitter and rear cell and for our 23.4%‐efficient ion‐implanted laser‐processed interdigitated back‐contacted cell. For the loss analysis of these two cells, we set all experimentally accessible control parameters (e.g., saturation current densities, sheet resistances, and carrier lifetimes) one at a time to ideal values. The efficiency gap to the ultimate limit of 29% is thereby fully explained in terms of both individual improvements and their respective synergistic effects. This approach allows comparing loss structures of different types of solar cells, for example, passivated emitter and rear cell and interdigitated back‐contacted cells. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : We demonstrate the synergistic efficiency gain analysis for an experimental passivated emitter and rear cell and an interdigitated back contacted cell. We model the transport and the optics of both cells using experimentally easily accessible input parameters (e.g., sheet resistances and saturation current densities). Synergistic efficiency gain analysis treats resistive, optical, and recombinative losses on equal footing, gives a breakdown of the full efficiency gap to the ultimate efficiency limit 29%, and can be carried out within minutes on a laptop.